Collective behavior and virulence arsenal of the fish pathogen Piscirickettsia salmonis in the biofilm realm - Levipan, Héctor A.; Irgang, Rute; Opazo, L. Felipe; Araya-León, Henry; Avendaño-Herrera, Ruben (Frontiers in Cellular and Infection Microbiology, 2022)
Piscirickettsiosis is a fish disease caused by the Gram-negative bacterium Piscirickettsia salmonis. This disease has a high socio-economic impact on the Chilean salmonid aquaculture industry. The bacterium has a cryptic character in the environment and their main reservoirs are yet unknown. Bacterial biofilms represent a ubiquitous mechanism of cell persistence in diverse natural environments and a risk factor for the pathogenesis of several infectious diseases, but their microbiological significance for waterborne veterinary diseases, including piscirickettsiosis, have seldom been evaluated. This study analyzed the in vitro biofilm behavior of P. salmonis LF-89T (genogroup LF-89) and CA5 (genogroup EM-90) using a multi-method approach and elucidated the potential arsenal of virulence of the P. salmonis LF-89T type strain in its biofilm state. P. salmonis exhibited a quick kinetics of biofilm formation that followed a multi-step and highly strain-dependent process. There were no major differences in enzymatic profiles or significant differences in cytotoxicity (as tested on the Chinook salmon embryo cell line) between biofilm-derived bacteria and planktonic equivalents. The potential arsenal of virulence of P. salmonis LF-89T in biofilms, as determined by whole-transcriptome sequencing and differential gene expression analysis, consisted of genes involved in cell adhesion, polysaccharide biosynthesis, transcriptional regulation, and gene mobility, among others. Importantly, the global gene expression profiles of P. salmonis LF-89T were not enriched with virulence-related genes upregulated in biofilm development stages at 24 and 48 h. An enrichment in virulence-related genes exclusively expressed in biofilms was also undetected. These results indicate that early and mature biofilm development stages of P. salmonis LF-89T were transcriptionally no more virulent than their planktonic counterparts, which was supported by cytotoxic trials, which, in turn, revealed that both modes of growth induced important and very similar levels of cytotoxicity on the salmon cell line. Our results suggest that the aforementioned biofilm development stages do not represent hot spots of virulence compared with planktonic counterparts. This study provides the first transcriptomic catalogue to select specific genes that could be useful to prevent or control the (in vitro and/or in vivo) adherence and/or biofilm formation by P. salmonis and gain further insights into piscirickettsiosis pathogenesis.